Load Shedding in High-Integrated Wind Energy Power Systems Using Voltage Electrical Distance - Tran, T. G.; Nguyen, T. A.; Nguyen Hoang, M. V.; Nguyen, N. A.; Tran, T. T. (Engineering, Technology & Applied Science Research, 2022)
This paper presents a load shedding method for power systems with high integration of wind energy, considering their frequency response. The minimum load shedding power needed to restore system frequency to operational limits can be determined by using the modified frequency response model along with secondary frequency control. The voltage electrical distance method can then be applied to appropriately distribute the shedding power to load buses. This method brings selectivity to the problem and minimizes the impact caused by load shedding. The proposed method was validated using simulations on the IEEE 37-bus test system with a modified wind power generator model.